Spawning induction and larval rearing of the sea cucumber Holothuria scabra in Malaysia - Mazlan, Nurzafirah; Hashim, Ridzwan (SPC Beche-de-mer Information Bulletin, 2015)
The sea cucumber Holothuria scabra was induced to spawn by the methods of thermal and algal stimulation. Thermal stimulation proved to be the better method. The larvae were given a mix of microalgal diet, the concentration of which was based on the larval growth. Doliolaria larvae appeared 11 days after fertilisation, and then became pentactula 18 days after fertilisation. A survival rate of 4.2% was recorded from three successful spawning.